The Influence Of Environmental Factors And Content Personalization On Consumer Engagement In Marketing Campaigns With Consumer Perceived Value As A Mediator - Lintang Anis Bena Kinanti; Santo Dewatmoko; Fatimah Abdillah (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2023)
In the rapidly evolving landscape of marketing, understanding the intricate interplay between environmental factors, content personalization, and consumer engagement has become pivotal for businesses. This study, conducted at PT. Bentoel Group (Asmo Jember), delves into the unique dynamics shaping consumer engagement within the framework of marketing campaigns. The research explores the direct and indirect relationships between Environmental Factors (EF), Content Personalization (CP), Consumer Perceived Value (CPV), and Consumer Engagement (CE).The direct paths analysis reveals significant impacts of both EF and CP on CPV, with CP demonstrating a robust influence. While the direct effect of EF on CE is not statistically significant, CP exhibits a significant influence on CE, emphasizing the strategic importance of tailored content in driving consumer engagement. The indirect paths analysis further uncovers meaningful insights, indicating that both EF and CP exert a significant indirect influence on CE through the mediating role of CPV.This study contributes valuable insights to the field of marketing, offering practical implications for businesses navigating the complex terrain of contemporary marketing. The findings provide PT. Bentoel Group with actionable recommendations to optimize marketing strategies, emphasizing the significance of content personalization and the nuanced impact of environmental factors in fostering enhanced consumer engagement and sustained brand loyalty..